Power-Effective Vedic-Hierarchical Multiplier - Moon Cheng, Wong; Arshad, Mohd Rizal (International Journal of Integrated Engineering, 2020)
The motivation of this project is to design a power effective multiplier without having much drawback in term of time constraint and area utilization. This is due to the overall power dissipation which increases in direct proportion to the increase in power density. The area and time constraint are considered as pertinent design parameters with the increase in market demand for high performance and complex portable systems. The current hierarchical multiplier designs suffer on long critical path and large area utilization. These parameters caused the hierarchical multiplier design to be less effective in term of power saving. The objective of this research is to reduce overall power dissipation and ensure that the multiplier achieve timing requirement. This paper proposes the design 1 by using two 4-bit Binary-to-Excess-One Converter (BEC) instead of an 8-bit BEC. The BEC reduce the critical path and cause low power dissipation. Design 2 which is implementation of Carry Select Adder (CSlA) with tristate buffer is to reduce logic elements. The power dissipation is reduced because of the decrease in the number of logic elements which leads to the lower number of logic gates. Both advantages of design 1 and design 2 are combined to become design 3. Design 3 is the lowest power dissipation design because it consists of the lowest number of logic elements and the shortest critical path. The timing requirement for all designs are met as shown by the positive slack time of 9.034 ns, 8.686 ns and 9.404 ns respectively. The power dissipation of the combinational multipliers designs have been improved to 60.96%, 60.89% and 61.02% respectively.